PERAN DINAS PENDIDIKAN PROVINSI SULAWESI BARAT DALAM MENGIMPLEMENTASIKAN STANDAR PROSES DI SEKOLAH MENENGAH KEJURUAN (SMK) SULAWESI BARAT - Tri Wahyuni Pattola (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2021)
This article discusses to find out how the Role of the Education Office in implementing process standards in vocational high schools (SMK) West Sulawesi, and at the same time to find out the obstacles or obstacles (weaknesses) faced by the Education Office in implementing process standards in vocational high schools (SMK) West Sulawesi. The type of research used in this research is descriptive research with a qualitative approach. The reason the researcher uses a qualitative approach is because he wants to get real experience from the meaning under study, meaning that he wants to know the situation of certain factors as actors who carry out certain jobs, certain situations, in certain places, so that researchers can understand the specific situation that is the object of research. This is very important in the analysis which will be used as the basis for making conclusions from the research. This research is focused on describing the implementation of process standards and revealing the role of the West Sulawesi Provincial Office. Based on research in the field, it shows that the role of the provincial education office, in this case the supervisor in implementing process standards at Vocational High Schools in West Sulawesi, has carried out his duties and functions of mentoring.